Upaya Meningkatkan Hasil Belajar Melalui Model Pembelajaran Cooperative Script Pada Mata Pelajaran Pendidikan Pancasila Peserta Didik Kelas XI SMK Widya Praja Ungaran - Roudhotun Naim; Abdul Karim; M. Lutfi Baehaqi (Lembaga Einstein College (LEC), 2025)
This research is motivated by the results of daily test learning of students in the subject of Pancasila education, where only 36.36% (8 students) achieved the Learning Objective Achievement Criteria (KKTP) from 22 students of class XI Culinary 1 SMK Widya Praja Ungaran. The research model used is Classroom Action Research (CAR), which is carried out collaboratively between researchers and subject teachers. This research was conducted in two cycles, where each cycle consists of the planning stage, action implementation, observation, and reflection. This research aims to improve students' daily test learning outcomes and teacher skills as well as students' activities in the subject of Pancasila education through the Cooperative Script learning model of class XI Culinary I students of SMK Widya Praja Ungaran. The results of the study used classroom action research (CAR) on class XI Culinary I students of SMK Widya Praja Ungaran. In cycle I, the learning outcomes of Pancasila education subjects with the Cooperative Script model increased to 81.82%, or 18 students, and in cycle II, the completeness increased to 90.91%, or 20 students. Teacher skills in cycle 1 received a score of 84.21%, classified as